Peranan Pendidikan Islam Dalam Membumikan Wawasan Kewirausahaan di Indonesia - Ahmad Darmadji (Universitas Islam Indonesia, 2012)
It has been a long time that education in Indonesia is under the challenge of both, globalization and unemployment. Enterpreuneship therefore is believed to be a solution to create creative, smart and independent generation. This article discusses the concept of enterpreunership in Islamic perspective and its relevance to Islamic education, it is colcluded that Islam in the position that supports for the development of enterpreunership, including the internatization of enterpreunesrship values in education. In the process of integrating of enterpreunership with education, education institutions may adopt a new method that will maintain that Islamic education is always relevant and applicable.Keywords: Islamic education, Entrepreneurship, independence